أثر استخدام التعزيز اللفظي في تعلم بعض المهارات الحركية للطلاب بطيئي التعلم - حسين, سها علي (Sulaimani Journal for Humanities, 2018)
The search included an introduction and the importance of research. The researcher pointed out of the importance of verbal reinforcement in learning motor skill for student slow learners. The research problem is that the student slow learners don't have the same ability to receive and understand the information during the learning, this leading to the obstruction of the learning process and their need for a period for a long time, so they need the means and methods to help them, among those methods is the verbal reinforcement. The researcher used the experimental method, experimental and control group with pre and post tests, research sample consisted of ten student of male and female five males and five females in the school for slow learners. The researcher apply the skills tests (front roll, dribble ball, jump). The use of the bag Statistical get search results. The researcher concluded that to enhance verbal significant impact in learning the skills required. The researcher recommended the need to the attention of the teachers in this segment and the use of verbal reinforcement being one of the basic requirements in the learning process.